AI IN YOUR MUNICIPALITY IMPLEMENTATION AND GOVERNANCE: Move beyond the hype to thoughtful AI adoption that serves your community's priorities. - PFEIFFER, MARC (Public Management (00333611), 2026)
The article presents guidance for municipalities on implementing and governing artificial intelligence applications. Topics include approaches to AI adoption and governance; best practices for staff training, accessibility, and vendor management; and strategies for building public trust and measuring successful outcomes.